Effect of Nutrition Education with Video Media for Student Knowledge of Snack Selection in Muhammadiyah 10 Surakarta Junior High School - Mery Anestya; Muwakhidah Muwakhidah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
Adolescence need adequate energy intake to support their physical and psychology development, one of them was obtained for snack consumtion in school. Election of food snacks was influenced by student knowledge. There are 30% students who have bad knowlegde. Aim of this research is for knowing effect nutritional education using video media for student knowledge of snack selection in Muhammadiyah 10 Surakarta Junior High School. This research using quasy eksperiment design with one grup pretest-posttest. Taking of sample using proportionate random sampling with total sample are 44 students. In this research using video media. Data analysis using Kolmogorov smirnov and Paired sample T-Test. Based on data analysis using Paired sample T-Test got result p = 0.000 it shows p 0.005 so H0 is refused it means there is any effect after giving nutrition education using video media. Mean score of students after giving nutrition education increase from 75,6 become 87. The conclusion is any effect nutrition education using video media for student knowledge in Muhammadiyah 10 Surakarta Junior High School.